Validating the Customer Satisfaction Survey (CSS) Scale in the Australian Fast Food Industry. Issue 3 (August 2013) - Phau, Ian; Ferguson, Graham
The aim of this study is twofold and is conducted in two separate studies. The first study validated the Customer Satisfaction Survey (CSS) Scale in the fast food industry with an Australian sample.Nicholls et al. (1998) developed the CSS as a way to assess key service elements. The authors tested it in multiple service industries andGilbert et al. (2004) tested it across cultures. Both sets of authors argued that the tool was universal irrespective of service industry or culture. Similar to previous findings, this current study found that personal service and service setting are key dimensions of satisfaction. However Australian consumers also assess whether service providers are delivering on their promises as part of assessing satisfaction. The second study compared CSS responses collected immediately following the service encounter to those collected after a temporal delay. After a delay customers used more items to assess each dimension but assessed satisfaction on similar dimensions. Managerial implications are discussed together with future directions.